Priority scheduling approach for heterogeneous systems in an intelligent building environment - Soozaei, Ahmad Shahi; Sulaiman, Md. Nasir; Mustapha, Norwati; Perumal, Thinagaran (Science and Knowledge Research Society, 2015)
Conflict is an unpredictable behavior which happens in intelligent building environment. Most of the works developed in intelligent building environments are towards higher layer hierarchy implementation (i.e. user and application layers) of system which dealt and interleaved with users and inhabitants preferences. However, to achieve the better interoperability among heterogeneous systems in lower layer hierarchy (i.e. sensors and devices), when an event(s) is received from building server, it may active more than one systems to be triggered in the same time which cause a conflict. Therefore, there is a necessity to propose a framework to solve the conflict occurrence among heterogeneous systems to have stable and efficient intelligent building.